The Effect of Good Corporate Governance on Firm Value with Earnings Quality as A Moderated Variables - Gusti Eka Setiawati; Muhammad Ali; Kasman Damang (Magister Management, Hasanuddin University, 2021)
Corporate governance is a concept to improve management performance by monitoring to ensure management accountability to shareholders. Besides being able to reduce agency conflicts, corporate governance is also capable of creating added value for interested parties (stakeholders) in the form of effective protection, especially for investors in recovering their investment fairly and of high value. The purpose of this study is to analyze the effect of managerial ownership, institutional ownership, and audit committee on firm value, and to analyze whether earnings quality can moderate the influence of managerial ownership, institutional ownership, and audit committee on firm value in banking companies listed on the IDX in 2017 -2019. The research population is banking companies listed on the IDX, with a purposive sampling technique, a total of 9 samples were obtained with the observation period 2017 to 2019. Data collection is through documentation obtained from the official website of the Indonesia Stock Exchange (IDX). Meanwhile, the data analysis technique used classical assumption test, multiple regression analysis, and moderated analysis. The results of the study found that managerial ownership and institutional ownership have a positive and significant effect on firm value. The audit committee has a negative and insignificant effect on firm value. Earnings quality cannot moderate the effect of managerial ownership, institutional ownership, and audit committee on firm value.